Assessment of thermosonication as postharvest treatment applied on whole tomato fruits: optimization and validation - Pinheiro, Joaquina (2020)
Tomatoes are a popular and rich fruit due to their nutritional and bioactive composition as vitamins, antioxidants, and phenolics contributing to the promotion of consumer health. For this reason, emerging postharvest technologies need to be evaluated to achieve the maintenance of sensorial and quality-related characteristics, like color and texture, while aiding to fruit decontamination. Optimization of thermosonication as postharvest treatments on whole, mature-green tomatoes (cv. “Zinac”) to improve quality (color, texture, total phenolic content, and weight loss) was performed by response surface methodology. Temperature (32–48 °C), treatment time (13–47 min), and storage period at 10 °C (1–15 days) at constant ultrasound frequency (45 kHz; 80% power level), were the independent variables. In general, thermosonication delayed tomato color changes while achieving total phenolic content increase and good overall quality. Three optimal thermosonication conditions were selected and validated (32 °C-13 min, 35 °C-20 min and 40 °C-30 min). The most suitable thermosonication condition that promoted a longer storage while keeping a high-quality standard was at 40 °C during 30 min. This study demonstrated that thermosonication provides an effective alternative methodology to guarantee tomato quality without significant change during the expected postharvest period.